Effects of doping with a third element (Pd, Ru, Ta) on the structure and hydrogen permeation properties of V–10Mo solid solutions. (7th February 2020) - Yan, Xiao Feng; Wang, Zhongmin; Wang, Feng; Chen, Taijun; Yao, Qingrong; Deng, Jianqiu; Zhou, Huaiying
Abstract: Alloying is an effective method for improving the resistance of V metals to hydrogen embrittlement. The effects of the doping with a third element (Pd, Ru, Ta) on the structure and hydrogen permeation properties of V–10Mo solid solutions have been investigated in this study. As-prepared V–5Mo-5TM (TM = Mo, Pd, Ru, Ta) alloy samples composed of V-based solid solution with a bcc structure are hydrogenated into their corresponding solid solutions (α-phase). Structural changes caused by TM-doping have notable effects on the hydrogen permeation properties (particularly the hydrogen solubility) of V–10Mo alloy, and the ability of the doping element in decreasing the hydrogen solubility of the V–10Mo alloy follows the sequence: Pd > Ru > Ta. Their doping causes a slight decrease in the hydrogen diffusion coefficient as well as an increase in the Vickers hardness of the resulting alloys. This work demonstrates that the mechanical property of V–10Mo alloy can be improved via suitable structure control caused by alloying it with an appropriate element. In addition, this approach might be suitable for improving properties of other relevant binary alloys. Highlights: Alloying do good to the resistance to hydrogen embrittlement of V metal. Hydrogen diffusivity and solubility are closely related to lattice distortions. Hydrogen permeability can be controlled by changing alloy composition and structure.